Marketing for beginners a case-study in retail - Lovering, Matthew; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2001)
Small businesses often focus on a very specific market niche. It helps them stand out in the crowded streetscape of shops. This case-study compares retail operations of two shops run by two brothers in two very different locations using a common product base - textiles imported from Guatemala. An expert in small business management assesses the marketing approach of the company and discusses more effective marketing strategies.
Narrator: Peter Kent
Keywords: Marketing -- Australia -- Case studies; Retail trade -- Australia -- Case studies